Patient Satisfaction is a Mediator of the Relationship between Human Resource Interaction, Service Quality, Trust, and Patient Loyalty - Panji Aryandaru; Herni Justiana Astuti; Bima Cinintya Pratama; Muchammad Agung Miftahuddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of human resource interaction, service quality, and trust on patient loyalty mediated by patient satisfaction at PKU Muhammadiyah Gombong General Hospital, PKU Muhammadiyah Amanah Sumpiuh General Hospital, and PKU Muhammadiyah Aghisna Kroya General Hospital. This study used a quantitative method with a survey approach, involving 200 patient respondents consisting of 100 patient respondents from PKU Muhammadiyah Gombong General Hospital, 50 patient respondents from PKU Muhammadiyah Amanah Sumpiuh General Hospital, and 50 patient respondents from PKU Muhammadiyah Aghisna Kroya General Hospital, reflecting institutional patient volume differences. Although the overall sample size is adequate for PLS-SEM, the disproportionate allocation across hospitals and the absence of explicit controls for institutional characteristics (such as hospital size, service scope, and patient demographics) may limit the comparability of hospital specific effects and constrain the generalizability of the findings to each organizational context. Respondents filled out a questionnaire related to their perceptions of human resource interaction, service quality, trust, satisfaction, and loyalty. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique with the help of Smart PLS software. The results showed that human resource interaction had no effect on satisfaction. Human resource interaction and service quality also had no effect on loyalty. Service quality and trust had a positive and significant effect on satisfaction. Trust and satisfaction had a positive and significant effect on loyalty. Patient satisfaction could mediate service quality and trust on loyalty. However, it did not for human resource interaction on loyalty.